Scientific Misconduct and Theft: Case Report from 17th Century - Fatović-Ferenčić, Stella (Croatian Medical Schools, 2008)
Gjuro Armen Baglivi was one of the most famous medical authorities of the 17th century. Apart from his numerous books and publications, several extensive collections of his correspondence have been preserved and are available in libraries around the world. They provide new information about the 17th century scientific culture and place of Baglivi’s work in the scientific European context. Also, they shed light on his personality more than other writings intended for the public eye. In this paper I will present the case of a theft of intellectual property, which Baglivi described in one of his letters to Jean Jacques Manget.